Design and Study of Stand-alone Multilevel Inverter Based on Switch Reduction Technique Fed by Photovoltaic and Wind Turbine Systems - Falah Jaber Kshash (Wasit Journal of Engineering Sciences)
Electricity stability is decreased and both harmonics and losses are increased throughout the power conversion procedures.  The drawbacks of conventional inverters may be addressed with the help of new multilayer inverter designs. Lately, multilevel inverter techniques have become more and more well-liked as an affordable substitute for a range of industrial uses. Several notable characteristics of this design include its smaller component, decreased switching losses, and improved output voltage/current pattern. The most crucial prerequisite for multilayer inverters is the minimization of harmonic components in the output voltage/current. The three distinct power sources that make up the system proposed in the present research are two identical wind turbines and photovoltaic system. Each of these power sources has an output voltage of 1, 2/3, and 1/3 Vdc, respectively. A 7-level output voltage was created by combining all of the DC sources. This paper proposes several situations, all of which have harmonic distortion within acceptable limits, and shows that the suggested system can function even in the event that one of the aforementioned power sources is unavailable. The MATLAB application is used to develop the system.